PENERAPAN METODE TOPSIS DALAM SISTEM PENDUKUNG KEPUTUSAN PROMOSI KENAIKAN JABATAN - RUSTAM, MUHAMMAD TAUFIQ (STMIK KAPUTAMA, 2019)
Determining the success of the company's work is influenced by the management of human resources (HR), one of the strategies in improving the quality of work of human resources by carrying out promotions. The method used in determining the promotion of promotion is the TOPSIS Method, it is expected that the assessment will be more appropriate because it is based on the criteria and weight values that have been determined so that it will get more accurate results. For that researchers try to help the problems mentioned above by making a decision support system using the PHP Programming Language with MySQL Database, so that the Application of the TOPSIS Method for this system can provide maximum results in terms of decision making.